1945-1965 Een Overzicht : Van Cobra tot Zero - Realisten - Beeldhouwers en Grafici - Redeker, Hans; Van Beek, Marius; Museum Van Bommel Van Dam, Venlo; Cultureel Centrum, Venlo; Galerie de Hoeve, Venlo (Venlo : Uitgeverij Van Spijk B.V., 1982)
Appel, Karel ; Benner, Gerrit ; Brands, Eugène ; Constant ; Corneille ; Lucebert ; Nieuwenhuys, Jan ; Rooskens, Anton ; Wolvecamp, Theo ; Westerik, Co ; Fernhout, Edgar ; Molenkamp, Nico ; Lataster, Ger ; Sierhuis, Jan ; van Soest, Pierre ; Wagemaker, Jaap ; etc.
drieluik-tentoonstelling: van Bommel van Dam, Venlo, Cultureel Centrum, Venlo, Galerie de Hoeve, Venlo
Nederlands
kunstcatalogus